MicroRNA-20a inhibits stress-induced cardiomyocyte apoptosis involving its novel target Egln3/PHD3 - Frank, Derk; Gantenberg, Johanne; Boomgaarden, Inka; Kuhn, Christina; Will, Rainer D.; Jarr, Kai-Uwe; Eden, Matthias; Kramer, Kristin; Lüdde, Mark; Mairbäurl, Heimo; Katus, Hugo; Frey, Norbert (Journal of molecular and cellular cardiology, 2012)
Excessive stress, e.g. due to biomechanical overload or ischemia/reperfusion is a potent inductor of cardiomyocyte apoptosis, which contributes to maladaptive remodeling. Despite substantial progress in the understanding of the molecular pathophysiology, many components of the signaling pathways underlying remodeling in general and apoptosis in particular still remain unknown. Recent evidence suggests that microRNAs (miRs) play an important role in the heart's response to increased cardiac stress. To identify novel modulators of stress-dependent remodeling, we conducted a genome-wide miR-screen of mechanically stretched neonatal rat cardiomyocytes (NRCM). Out of 351 miRs, eight were significantly regulated by biomechanical stress, including microRNA-20a, which is part of the miR17-92 cluster. Interestingly, further expression analyses also revealed upregulation of microRNA-20a in an in vitro hypoxia/“reperfusion” model. Given the potential apoptosis-modulating properties of the miR17-92 cluster, we subjected NRCM to hypoxia and subsequent reoxygenation. AdmiR-20a significantly inhibited hypoxia-mediated apoptosis in a dose-dependent fashion, while targeted knockdown of miR-20a in NRCM induced cardiomyocyte apoptosis. Mechanistically, the antiapoptotic effect of miR-20a appears to be mediated through direct targeting and subsequent downregulation of the proapoptotic factor Egln3. Thus, miR-20a is upregulated in acute biomechanical stress as well as hypoxia and inhibits apoptosis in cardiomyocytes. These properties reveal miR-20a as a cardioprotective micro-RNA and a potential target for novel therapeutic strategies to prevent cardiac remodeling.